Evaluasi Unsafe Action, Unsafe Condition, Near Miss, Safe Action, Safe Condition pada Pekerja Dibagian Operasional di PT Syngenta Seed Indonesia (Menggunakan Gensuite Observation) - Alkaf Mu’nis Bahsin; Abdul Rohim Tualeka (Universitas Malahayati Lampung, 2024)
ABSTRACT Labor is one of the most important components in the implementation of workers and is a determining asset for the company. The increase in work accidents in ordinary work environments is due to incidents of unsafe actions, unsafe conditions and near misses among workers. With the HSE main rule observation program, it is a safety campaign for the company. Observation and evaluation of the number of unsafe actions, unsafe conditions, near misses, safe actions, safe conditions as an indicator of the company's success in implementing zero accidents at PT SSI. Descriptive with an observational approach, using a questionnaire inputted to the web (Gensuite Observation). Using primary data from interviews in the field and secondary data obtained through research-related documents. Gensuite Observation for the period January – June in 2022 in the operational section (HSE, processing, warehouse) found 297 findings, while in 2023 there were 260 findings, where this year there was a decrease in findings by 37. Comparison of Gensuite Observation results in 2022 and 2023 for the HSE section there was an increase in new findings of 6 findings (15 to 21), a comparison of the results of Gensuite Observations in 2022 and 2023 for the Processing section showed a decrease in findings of 9 (158 to 149), a comparison of the results of Gensuite Observations in 2022 and 2023 for the Warehouse obtained the same finding value 0 findings (30 to 30). The results of research at PT SSI show that corrective action has been taken. The final process of SMK3 is corrective action from the results of audits and performance evaluations that have been carried out as an effort to prevent unsafe actions, unsafe conditions, near misses, safe actions, safe conditions from occurring in the company environment. Keywords: Occupational Health and Safety, Observation and Reporting of HSE Rules, Unsafe Action, Unsafe Condition, Near Miss. Gensuite Observation ABSTRAK Tenaga kerja merupakan salah satu komponen terpenting dalam pelaksanaan pekerja dan merupakan aset yang menentukan bagi perusahaan. Terjadinya peningkatan kecelakaan kerja di lingkungan kerja biasa disebabkan adanya kejadian unsafe action, unsafe condition, near miss pada pekerja. Dengan adanya program pengamatan aturan utama (health safety Environment) HSE merupakan salah satu safety campaign bagi perusahaan. Pengamatan dan evaluasi angka kejadian unsafe action, unsafe condition, near miss, safe action, safe condition sebagai alat indikator keberhasilan perusahaan dalam melaksanakan zero accident di PT SSI. Deskriptif dengan pendekatan observasi, dengan menggunakan kuesioner yang diinput ke web (Gensuite Observation). Menggunakan data primer hasil wawancara dilapangan dan data sekunder di peroleh melalui dokumen terkait penelitian. Gensuite Observation periode januari – juni pada tahun 2022 pada bagian operasional (HSE, processing, warehouse) didapatkan sebanyak 297 temuan sedangkan di tahun 2023 sebanyak 260 temuan, dimana pada tahun ini mengalami penurunan temuan sebanyak 37. Perbandingan hasil Gensuite Observation pada tahun 2022 dan 2023 untuk bagian HSE didapatkan peningkatan temuan baru sebanyak 6 temuan (15 ke 21), perbandingan hasil Gensuite Observation pada tahun 2022 dan 2023 untuk bagian Processing didapatkan penurunan temuan sebanyak 9 (158 ke 149), Perbandingan hasil Gensuite Observation pada tahun 2022 dan 2023 untuk bagian Warehouse didapatkan nilai temuan yang sama 0 temuan (30 ke 30). Hasil penelitian di PT SSI menunjukkan bahwa tindakan perbaikan sudah dilakukan. Proses akhir dari SMK3 adalah tindakan perbaikan dari hasil audit maupun evaluasi kinerja yang telah dilakukan sebagai upaya dalam pencegahan terjadi suatu tindakan unsafe action, unsafe condition, near miss, safe action, safe condition yang terjadi di lingkungan perusahaan. Kata Kunci: Kesehatan dan Keselamatan Kerja, Pengamatan serta Pelaporan Aturan HSE, Unsafe Action, Unsafe Condition, Near Miss, Gensuite Observation